THE PHENOMENON OF VOWEL HARMONY IN THE TASHKENT DIALECT (American Journal of Interdisciplinary Research and Development, 2025)
This article presents perspectives on the classification of Uzbek dialects, scholars’ views on dialects that preserve vowel harmony and insights into the phonetic characteristics of the Tashkent dialect, including how vowel harmony is maintained in this particular dialect.